Tillage system and seeding rate effects on the performance of Brassica carinata. Issue 4 (9th February 2021) - Iboyi, Joseph E.; Mulvaney, Michael J.; Balkcom, Kipling S.; Seepaul, Ramdeo; Bashyal, Mahesh; Perondi, Daniel; Leon, Ramon G.; Devkota, Pratap; Small, Ian M.; George, Sheeja; Wright, David L.
Abstract: Brassica carinata, a nonfood oilseed crop, is used to produce renewable fuels because of its high oil content and favorable fatty acid profile. Production in the southeastern United States is relatively new, and information on agronomic management practices to optimize growth and yield is limited. Since optimal seeding rate may depend on the land preparation method for this small‐seeded crop, a study was conducted to evaluate the effect of tillage system (conventional, no‐till, broadcast‐disc, and ripper‐roller) and seeding rate (1.12, 5.60, 10.09, and 14.57 kg seed ha −1 ) on the performance of B. carinata . A randomized complete block design with a strip‐plot restriction on randomization and four replications was implemented in Headland, AL, Jay, FL, and Quincy, FL, over five site‐years during the 2017–2018 and 2018–2019 growing seasons. Data were collected on soil residue cover; plant population; soil penetrometer resistance and moisture; biomass (including carbon and nitrogen); stalk diameter; yield and yield components; seed oil, protein, and glucosinolates concentration; and oil composition. Soil penetrometer resistance was significantly affected by tillage system, with the ripper‐roller consistently having the lowest penetration resistance values across all site‐years. Ripper‐roller tillage had the highest oil content and lowest protein and glucosinolate contents. Yield response to tillage system was variable. Among seeding rate treatments, yield was lowest at 1.12 kg seed ha −1 and similar among 5.60, 10.09, and 14.57 kg seed ha −1 at all site‐years. There was no tillage by seeding rate interaction for yield. Results indicate that among seeding rate treatments used, 5.6 kg seed ha −1 rate was optimal at all site‐years regardless of land preparation method and is thus the recommended seeding rate for commercial carinata production in the Southeastern United States. Abstract : Carinata commercialization was first introduced to the Southeastern United States in 2014 to be grown as a winter crop to produce jet fuel, seed meal, and other high‐value co‐products. However, several agronomic management issues related to production emerged, among which are tillage and seeding rates. These issues require resolution. A study was conducted over five site‐years to evaluate the effect of tillage system (conventional, no‐till, broadcast‐disc, and ripper‐roller) and seeding rate (1.12, 5.60, 10.09, and 14.57 kg seed ha −1 ) on the performance of carinata. Results indicate that among seeding rate treatments used, 5.6 kg seed ha −1 rate was optimal at all site‐years regardless of land preparation method.